Evaluation of anatomical characters and their applicability for reconstructing phylogenetic relationships in the Palaearctic species of Pisidium s. l. (Mollusca, Bivalvia) - Korniushin, A.V. (Вестник зоологии, 1998)
Anatomical study of the small clams traditionally included in the genus Pisidium revealed new taxonomically and phylo-genetically significant characters. Plesio- and apomorphic states are determined for these characters whenever possible. Synapomorphies in anatomical characters support some intrageneric groups established earlier and encourage to suggest the new affinities between species.